Análise da pressão de interface em três almofadas para cadeiras de rodas em sujeitos com lesão medular - Mendes, Paulo Vinicius Braga (2016)
Introduction: Pressure ulcers (PU) are common complications in patients with spinal cord injury (SCI). The peak pressure on the ischial region in individuals with SCI are higher than those found in subjects without physical disabilities and this fact is justified by sensitivity, motor and vasomotor changes. Objective: To compare the pressure distribution on the seat of the wheelchair of subjects with SCI using 3 different types of cushions (Roho®, Varilite® and Varilite®). Methodology: we selected 10 participants of both genders with SCI (n=05 tetraplegia and n=05 paraplegia). The analysis of the pressure on the seat was performed during two different situations: with the participant sitting in static posture and another step using the wheelchair for locomotion. Results: For the first step to Jay® showed the best rates for average pressure and also the contact area (p<0,001), the Roho® showed the best index for peak pressure (p<0,002). In the step with the wheelchair moving, Jay® showed the best average pressure (p<0,001), the Roho® had the lowest average for the peak pressure (p<0,002), and Varilite® provided the highest means for the contact area of the buttocks and thighs (p<0,006). All cushions evaluated showed lower values to those considered risk factors for PU, ratifying the importance of its use for the prevention. Conclusion: The use of cushions are effective measures to aid in the prevention of PU in people with SCI, but do not replace other ways of prevention. There is the need for proper cushion calibration and guidance on its use to get the desired effects.